Extraction and purification of recombinant single chain antibody recognizing blood antigens - Huong, Do Thu; Hai, Truong Nam; Hong, Le Thi Thu (Academia Journal of Biology, 2020)
In our previous study, we reported the expression of a recombinant single chain fragment variable (scFv) antibody that recognized blood type A antigen (antiA-scFv) in E. coli. When when it was expressed as it is alone, antiA-scFv was produced as inclusion body. In contrast, SM/antiA-scFv was synthesized in soluble form when it was fused to small ubiquitin modifier (SUMO). Here, we present the extraction and purification of antiA-scFv in the inclusion body as well as in the soluble form and evaluate the antiA-scFv antibody activity. The results show that only fusion expression of soluble SM/antiA-scFv has biological activity of the antibody. SM/antiA-scFv was separated by fractional precipitation with 20% ammonium sulfate, and then washed with buffers to collect the pure antiA-scFv with SUMOprotease treatment. The purity of recombinant antibody was 89% and the yield of 64.9 mg/L of bacterial culture. The antibody has a polymer structure and could bind to purified antigen as well as agglutinate with red blood cell, but the specificity of the antibody was not good enough for the antigen and red blood cell of blood type A. This is the first report in Vietnam showing the extraction and purification of the recombinant single chain antibody recognizing antigen of ABO system using E. coli expression system. It can be considered as a reference for further studies to improve the specificity of recombinant antibody antiA-scFv to identify ABO-type blood antigens.